Mapping Places of Encounter: An Integrative Methodological Approach to Understanding Social Inclusion - Spenger, David; Kordel, Stefan; Weidinger, Tobias (International Journal of Qualitative Methods, 2023)
Physical places of encounter are nodes of social interaction in which moments of social inclusion and exclusion crystallize. On a methodological level, meeting places have in the past usually been associated either with firmly established spatial arrangements or with situational opportunities of encounter. Acknowledging the complexity of places of encounter and developing further a spatio-visual mapping tool conducted in various research projects on local inclusion of newcomers, we propose an integrative research approach to capturing, mapping and analyzing places of encounter via four dimensions: level of institutionalization, level of intentionality, level of inclusion and horizontal and vertical scale. The proposed place-based approach holds the chance to explicitly take into account a spatial perspective in the analysis of social interactions. Thus, it goes beyond mere network analysis, but is able to capture the socio-spatial conditions of encounters as pre-configurations of further social dynamics. In doing so, we address not only the methodological gap in research but also the practical relevance for identifying and evaluating locally important meeting places. More specifically, as part of a qualitative interview, the mapping tool can enable the participation of people whose voices are seldom heard, while the inclusion of multiple perspectives on places of encounter may facilitate local governance processes in the social realm.<br
Keywords: Places of encounter; meeting places; social inclusion; mapping; qualitative research